Photography by Massinissa Garaoun | Linguistic fieldwork in North Africa | Place du Premier Novembre (formerly Place Gueydon) - (:unkn) unknown (My University, 2023)
This photograph has been captured by Massinissa Garaoun, in the coastal city of Béjaïa in Kabylia (Algeria).This was part of a linguistic survey to document Bougiote (lə-bǧawiya), an Arabic language formerly spoken in this coastal town. This Arabic is of a conservative pre-Hilalian type and is particularly marked by contact with Kabyle.
Keywords: African Research